(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the pedagogical possibilities of using digital technologies in the educational process. Also, the importance of digital technologies in increasing the effectiveness of education, their advantages and existing problems are highlighted. The article analyzes the issues of using multimedia tools, online platforms, social networks and electronic resources in the educational process. Based on the results of the research, practical proposals and recommendations on the effective use of digital technologies have been developed.